Uma Análise Experimental Sistemática do Envelhecimento e Rejuvenescimento da Plataforma Docker - Santos, Lucas; Rodrigues, Laécio; Torquato, Matheus; Silva, Francisco Airton (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance); 2020: Anais do XIX Workshop em Desempenho de Sistemas Computacionais e de ComunicaçãoDO - 10.5753/wperformance.2020.11112, 2020)
Software aging has been a subject explored for almost thirty years. Even with so many years of scientific research, new investigations will be needed due to new technologies. The Docker platform, for example, appeared in 2013 and, although it has been deeply explored, it still needs studies on software aging. Studies show that containers are lighter than virtual machines, however, running many containers can lead to aging. This paper presents a study of aging and rejuvenation of the Docker platform. An experiment was carried out for thirty days, which indicated different levels of aging by varying hardware capacity. We have applied an approach called SWARE. SWARE facilitates the detection of aging signs and rejuvenation effectiveness in a single experiment. Evidences have shown that resource consumption remains high after stopping the workload generation.